AMoRE experiment: a search for neutrinoless double beta decay of 100Mo isotope with 40Ca100 MoO4cryogenic scintillation detector - Bhang, Hyoung C.; Enss, Christian; Fleischmann, Andreas; Gastaldo, Loredana (Journal of physics. Conference Series, 2012)
AMoRE ( A dvanced Mo based R are process E xperiment) collaboration is going to use calcium molybdate crystals as cryogenic scintillation detector in a search for neutrinoless DBD of 100 Mo isotope. Simultaneous detection of phonons and light will be used to reject internal background. A FWHM resolution of 0.2% in the phonon channel has been achieved with a 0.5 cm 3 crystal. Several 40 Ca 100 MoO 4 crystals (≈ 0.5 kg) have been developed from enriched 100 Mo and depleted 40 Ca materials. The light yield of these crystals has been shown to be comparable with reference CaMoO 4 scintillators for temperatures ranging down to 8 K. The content of dangerous radioisotopes in the crystals is under measurement. The projected sensitivity of the experiment for a 250 kg × years exposure is lim T 1/2 3 × 10 26 years, which corresponds to the effective Majorana neutrino mass ##IMG## [http://ej.iop.org/icons/Entities/langle.gif] langle m v ##IMG## [http://ej.iop.org/icons/Entities/rangle.gif] rangle 0.02 - 0.06 eV.
Die Zahlen 100 und 40 sind hochgestellt und die Zahl 4 ist tiefgestellt
Gesehen am 09.01.2019